A Novel Mutation of VPS33B Gene Associated with Incomplete Arthrogryposis-Renal Dysfunction-Cholestasis Phenotype. (24th September 2020) - Agakidou, Eleni; Agakidis, Charalampos; Kambouris, Marios; Printza, Nicoleta; Farini, Maria; Vourda, Elina; Gerou, Spyridon; Sarafidis, Kosmas
Abstract : Arthrogryposis-renal dysfunction-cholestasis (ARC) syndrome is an autosomal recessive disorder caused by mutations of the V P S 33 B encoding the vacuolar protein sorting 33B (VPS33B), which is involved in the intracellular protein sorting and vesicular trafficking. We report a rare case of ARC syndrome without arthrogryposis caused by a novel mutation of V P S 33 B . A female patient of Greek origin presented on the 14 th day of life with renal tubular acidosis, Fanconi syndrome, nephrogenic diabetes insipidus, and cholestasis with normal gamma-glutamyl transpeptidase, without arthrogryposis and dysmorphic features. She was born to apparently healthy, nonconsanguineous parents. Additional features included dry and scaling skin, generalized hypotonia, hypoplastic corpus callosum, neurodevelopmental delay, failure to thrive, short stature, recurrent febrile episodes with and without infections, and gastrointestinal bleeding. DNA testing revealed that the patient was homozygous for the novel c.1098_1099delTG (p.Glu367Alafs∗ 17) mutation of exon 14 of V P S 33 B gene (NM_018668) on chromosome 15q26.1, leading to a nonsense frameshift variant of VPS33B with premature termination of translation. Her parents were heterozygous for the same V P S 33 B mutation. The prognosis was predictably poor in the context of the intractable polyuria necessitating long-term parenteral fluid administration via indwelling central catheter leading to catheter-related sepsis, to which she eventually succumbed at the age of 7 months. This is the first published V P S 33 B mutation in an ARC patient of Greek origin. The current case adds to the spectrum of ARC-associated V P S 33 B mutations and provides evidence supporting the existence of incomplete ARC phenotype. Increased awareness and early genetic testing for ARC are suggested in cases with isolated cholestasis and/or renal tubular dysfunction, even in the absence of arthrogryposis.